Erratum: A study on caffeine consumption and its association with stress and appetite among call centre employees in Mumbai city, India - Kale, Lakshmi B.; Reddy, Kejal Joshi (International Journal Of Community Medicine And Public Health, 2017)
In the online version of this article initially published, the affiliation details should have read as “Nutrition and Dietetics Department, Symbiosis School of Biomedical Sciences, Symbiosis International University, Lavale, Pune, Maharashtra, India”. Also, the correspondence email should have been “kejal.joshi@ssbs.edu.in” instead of kejaljoshi@gmail.com. In the Ethical approval section, a statement “The study was approved by the Institutional Ethics Committee of Research Advisory Committee (RAC)…” should have read as “The study was approved by the Research Advisory Committee (RAC) at Symbiosis School of Biomedical Sciences, Symbiosis International University, Pune, India.” The errors have been corrected in the PDF version of the article.